PENGEMBANGAN FLIPBOOK PADA MATERI INTEGRAL UNTUK PESERTA DIDIK KELAS XI SMA - Hamdani Syaputra (Departemen Matematika, 2022)
The teaching materials used by educators in classroom learning make students is not enough for the teaching. This causes low of student learning outcomes. Flipbooks are considered capable of improving the quality of classroom learning, improving the effectivity in learning, independent learning by students, and also the student learning outcomes, especially on integral material. This is because in addition to having features in the form of writing, there are also pictures, videos and other interesting features. This type of research is Research and Development (R&D) and using the Plomp model which produces valid and practical flipbooks on integral material. Flipbook on this integral material is very valid and very practical with a valid score of 85.95% and a practical score of 87.17% from students and 97.08% from educators. Keywords– Flipbook, Integral, Plomp, Practical, Valid